Durability is improved by both low and high intensity endurance training - Matomäki, P.; Heinonen, O. J.; Nummela, A.; Laukkanen, J.; Auvinen, E. P.; Pirkola, L.; Kyröläinen, H. (Frontiers in Physiology, 2023)
Introduction: This is one of the first intervention studies to examine how low- (LIT) and high-intensity endurance training (HIT) affect durability, defined as `time of onset and magnitude of deterioration in physiological-profiling characteristics over time during prolonged exercise`. Methods: Sedentary and recreationally active men (n = 16) and women (n = 19) completed either LIT (average weekly training time 6.8 ± 0.7 h) or HIT (1.6 ± 0.2 h) cycling for 10 weeks. Durability was analyzed before and after the training period from three factors during 3-h cycling at 48% of pretraining maximal oxygen uptake (VO2max): 1) by the magnitude and 2) onset of drifts (i.e. gradual change in energy expenditure, heart rate, rate of perceived exertion, ventilation, left ventricular ejection time, and stroke volume), 3) by the `physiological strain`, defined to be the absolute responses of heart rate and its variability, lactate, and rate of perceived exertion. Results: When all three factors were averaged the durability was improved similarly (time x group p = 0.42) in both groups (LIT: p = 0.03, g = 0.49; HIT: p = 0.01, g = 0.62). In the LIT group, magnitude of average of drifts and their onset did not reach statistically significance level of p < 0.05 (magnitude: 7.7 ± 6.8% vs. 6.3 ± 6.0%, p = 0.09, g = 0.27; onset: 106 ± 57 min vs. 131 ± 59 min, p = 0.08, g = 0.58), while averaged physiological strain improved (p = 0.01, g = 0.60). In HIT, both magnitude and onset decreased (magnitude: 8.8 ± 7.9% vs. 5.4 ± 6.7%, p = 0.03, g = 0.49; onset: 108 ± 54 min vs. 137 ± 57 min, p = 0.03, g = 0.61), and physiological strain improved (p = 0.005, g = 0.78). VO2max increased only after HIT (time x group p < 0.001, g = 1.51). Conclusion: Durability improved similarly by both LIT and HIT based on reduced physiological drifts, their postponed onsets, and changes in physiological strain. Despite durability enhanced among untrained people, a 10-week intervention did not alter drifts and their onsets in a large amount, even though it attenuated physiological strain.